Synthesis, absorption, distribution, metabolism, excretion and antioxidant assay of some N4 –substituted thiosemicarbazones of cinnamaldehyde - CIURSIN, Andrei; RUSNAC, Roman; GULEA, Aurelian (One Health & Risk Management, 2025)
Introduction. The increasing number of cancer diagnoses is a pressing issue in modern medicine. One contributing factor to cancer development is oxidative stress caused by free radicals, which can damage proteins, lipids, and DNA. Antioxidants are commonly used to mitigate these effects by neutralizing free radicals and reducing their harmful impact. Recent studies have shown that thiosemicarbazones may have antioxidant properties. These compounds are also known for their potential as anticancer, antibiotic, and antifungal agents. In this research, a series of thiosemicarbazones were synthesized and their antioxidant capacity was evaluated. Additionally, the ADME (Absorption, Distribution, Metabolism, Excretion) parameters of the synthesized compounds were evaluated to determine their potential as pharmaceutical candidates.Material and methods. All starting reagents were purchased from Sigma Aldrich or Alfa Aesar. The synthesis of the compounds was carried out using classical methods, adopted for this study. ADME analysis was performed using ADMETLabs 3.0 platform. Antioxidative properties were investigated using the standard assay method.Results. Five thiosemicarbazones were synthesized. The presence of characteristic functional groups was confirmed by FTIR spectroscopy. Synthesized compounds have a good ADME profile, characteristic of biologically active compounds. It was found that compounds 1 and 5 exhibit antioxidative activity in 6 times and 3 times higher than Trolox.Conclusions. Obtaining new thiosemicarbazones based on cinnamaldehyde with the study of antioxidant properties and ADME screening would allow in the future that these products can be tested in the clinical and preclinical stages with rigorous evaluations. The synthesized products represent an increased antioxidant potential for the biopharmaceutical field.